Teachers’ perceptions of the differential impacts of a universal, school-based social and emotional learning intervention: A thematic framework analysis - Suzanne Hamilton; Jan R. Boehnke; Neil Humphrey; Pamela Qualter (PLoS ONE, 2025)
Trials of universal school-based (USB) social and emotional learning (SEL) interventions have reported that individual and socio-demographic characteristics may moderate outcomes, but it is not clear how. Teachers are key stakeholders in SEL and are involved in the implementation of interventions, so they can offer insights into patterns of responsiveness and intervention impact. This qualitative study aimed to explore teachers’ perceptions of the differential impacts of the PATHS curriculum, a USB SEL intervention. Data were generated in semi-structured interviews with 105 implementing teachers as part of a trial of PATHS in 23 primary schools across Greater Manchester, and analysed using thematic framework analysis. Six main themes and 22 subthemes formed the final thematic framework. Teachers suggested that students demographic backgrounds influenced both engagement with and responsiveness to the intervention and that a certain initial level of social and emotional skills were needed as foundation on which to build further learning. The potential of teachers’ expectations and beliefs about pupils’ characteristics to impact on implementation quality and judgements of impact are discussed. Implications for practice and future research are considered.